Gestalt-terapia herança em re-vista - Gomes, Patrícia Wallerstein (2001)
This paper researches on the possible reasons which made the Gestalt-therapy show a fragile approach image, with no theoretical basis, and therefore easier to be dealt with since it wouldn´t demand a deep knowledge from the professional Gestalt-therapist. The author, here defining herself as heiress to this approach, rescues the Gestalt-therapy´s origin and concepts pointing out to the importance of its founders, Fritz and Laura Perls . She considers their beliefs, myths and personal values as well as their direct or indirect influence on the Gestalt-therapy´s destiny. This study, wich focus on the Gestalt-therapy very beginning, aims to clearly understand the social-cultural aspect and its demands, with the purpose of analysing the Gestalt-therapy and its concepts in a much broader context that makes it meaningful. This research is made up of interviews with three current Brazilian Gestalttherapists, who are also considered heirs, hence this autor´s brothers. The main goal for interviewing those therapists was not only to analyse their individual comprehension about Gestalt-therapy itself as theory but also to have their own opinion about the possible causes for today´s superficial approach of this therapy. This study highlits that a Gestalt-therapist needs theoretical and practical pillars that reveal and consider not only the influence undertaken by such a light Gestalttherapy approach but also that clarifies the concepts which this therapy makes use of. It is still paramount that one distinguishes between what Gestalt-therapy actually is from something that merely makes up its father s (Fritz Perls) way of being